Metagenome Sequencing Reveals the Microbiome of Aedes albopictus and Its Possible Relationship With Dengue Virus Susceptibility - Zhao, Teng; Li, Bo-qi; Gao, He-ting; Xing, Dan; Li, Man-jin; Dang, Yun-qi; Zhang, Heng-duan; Zhao, Yue-e; Liu, Zhu; Li, Chun-xiao (Frontiers in Microbiology, 2022)
Dengue fever virus (DENV) is a mosquito-borne flavivirus that poses a serious risk to human health. Aedes albopictus is a widely distributed vector of dengue fever in China. Based on the impact of physiological activity, the microbiome in A. albopictus will provide a novel environment-friendly approach to control DENV transmission. We performed metagenomic sequencing on A. albopictus before and after exposure to DENV blood meal to detect microbiome variation of A. albopictus with different susceptibilities to DENV. The dominant phyla in A. albopictus microbiome were Proteobacteria and Ascomycota, and the dominant genera were Aspergillus and Metarhizium. Gammaproteobacteria bacterium, Lactobacillus harbinensis, and Neurospora crassa differed significantly after DENV infection. There were 15 different microorganisms found to be involved in mosquito immunity and metabolism, such as Alphaproteobacteria bacterium, Methyloglobulus morosus, and Shigella sonnei, which might have an impact on the DENV susceptibility of A. albopictus. It was hypothesized that the lack of specific bacteria may lead to increased susceptibility of A. albopictus to DENV. Interventions in the microbiome composition or specific bacteria of A. albopictus may affect the susceptibility to DENV and control the mosquito-borne diseases efficiently.